STRATEGY FOR USING SOCIAL MEDIA AS A LEARNING TOOL TO DEVELOP DIGITAL LITERACY AMONG TEENAGERS - Seno Lamsir (Adisam Publisher, 2025)
This research aims to examine strategies for using social media as a learning tool in an effort to develop digital literacy among teenagers. The research method used is literature research by collecting and analyzing various relevant sources, including journals, articles and books that discuss this topic. The main findings of this research indicate that social media has great potential to be an effective learning platform for teenagers, given the high level of engagement and popularity among them. Effective strategies found include collaboration with educational technology and child psychology experts to ensure safe, engaging, and educational content. In addition, developing a healthy digital culture through education about digital ethics and online privacy is very important to maximize the use of social media. Support from governments and educational institutions, such as providing funding, teacher training, and partnerships with technology companies, was also identified as a key factor that can improve technology infrastructure and access to learning resources. With proper implementation, social media can be an effective tool for developing digital literacy among teenagers, preparing them to face the challenges of the digital era.